Comparative Stiffness Analysis of Treated vs Untreated Meshed Coir Fiber Reinforced Cement Concrete - R. Parthasaarathi; R. Sakthivel; R. Senthil Kumar (Science and Technology: Recent Updates and Future Prospects Vol. 9, 2024)
This study investigates the impact of meshed coconut coir on the mechanical and durability properties of coir-reinforced cement concrete, aiming to control internal and external cracks. The meshed form of coir is known for its ability to mitigate shrinkage, enhancing both strength and durability. Phase I of the experimental investigation involved preparing 49 samples: 28 cubes (150x150x150mm) and 21 beam prisms (100x100x500mm). The tests included water absorption, porosity, sorption rate for physical properties, acid and alkaline attack resistance for durability, and compression and flexural bending strength for mechanical properties. The coir was tested in treated and untreated forms, with single and double layers in the concrete. Results indicated that while compressive and flexural bending strengths showed modest improvements, post-crack properties such as ductility, residual strength, and toughness significantly increased with higher fractions of meshed coir. Meshed coir reinforcement, used in layers, is proportioned between 5% to 25%. This natural fiber enhances material strength and durability, offering an eco-friendly alternative for construction and manufacturing applications. Its usage improves structural integrity while promoting sustainability. The findings suggest that meshed coconut coir can be a valuable addition to concrete, providing better crack control and improving post-crack behavior.